Covenant, Universal Mission, and Fulfillment - Madges, William (Studies in Christian-Jewish Relations, 2017)
This article examines the theological relationship between Judaism and Christianity, as articulated in the 2015 document from the Pontifical Commission for Religious Relations with the Jews, entitled “The Gifts and the Calling of God are Irrevocable.” On one hand, the Vatican document re-affirms the positive estimation of Judaism expressed in the Second Vatican Council’s Nostra aetate (1965), and it rejects Christian replacement theology. On the other, it reiterates Pope Benedict XVI’s single-covenant understanding of the Jewish-Christian relationship, and it affirms a theology of fulfillment. Although a theology of fulfillment tends in the direction of supersessionism, the Vatican document contains resources for avoiding a re-lapse into supersessionism by using sibling language to describe the relationship and by emphasizing the uniqueness of each tradition.